Jan Marek Skuratowicz (1946–2024). Biografia nie tylko naukowa - Żuchowski, Tadeusz J. (Artium Quaestiones, 2024)
The article is a memoir of Prof. Jan Skuratowicz (1946–2024), a long-time employee of the Department of Art History at Adam Mickiewicz University in Poznań, Poland.